Ile jest pisarza w jego książkach? Na przykładzie wyboru z twórczości Jana Józefa Szczepańskiego = How much is the writer in his books? Based on the example of a selection from the works by Jan Józef Szczepański - Niewdana, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
How much is the author in his text, painting or sculpture? It would seem that such a question should not be asked, because here it is the work itself that counts. The author could be completely ignored or only mentioned; a short biographical note did not really bring anything relevant in the context of the discussed piece of his work. However, for me, the figure behind the signature on a book or under a photograph always mattered. A special case in this situation is the Krakow-based writer Jan Józef Szczepański. A few years ago, an expert and researcher of Conrad, but also of the author of "Polish Autumn" [Polska jesień], proposed an autobiographical reading of Szczepański`s work.
Keywords: Szczepański, Jan Józef (1919-2003); Szczepański, Jan Józef (1919-2003) - Portki Odyssa; autobiografizm; biografia; autor; pisarz polski; autobiography; biography; author; writer